Lipase Activity Enhancement of KC4J Mutant from Oil Palm Waste Using Response Surface Method and Characterization. - Aris Indriawan; Trismilah .; Wibowo Mangunwardoyo; Dadang Suhendar (Microbiology Indonesia, 2022)
Lipase has an important role in industry. The KC4J mutated isolates from oil palm waste had 100% similarity to Aspergillus fumigatus strain RA204, a fungus known produce lipase. The study aimed to increase lipase activity of KC4J mutant through media optimization using Response Surface Methodology (RSM) and partial characterization. The three variables of media composition (olive oil, soy flour, and pH were optimized using Central Composite Design (CCD). The lipase characterization measured the influence of pH, temperature and metal ions. The pH tested on range 6 to 12, while the temperature variation tested on 30 to 70 °C. The metal ions tested were Mg2+, Ca2+, Zn2+, Mn2+, Fe2+ and K+ with concentrations of 1 mM and 10 mM. The production medium containing 1.25% of olive oil, 3.5% of soy flour and 7.5 pH resulting 11.25 U/mL of Lipase activity, which was higher than the previous media composition (10.00 U/mL). The results of CCD and quadratic analysis showed that the source of carbon, nitrogen and pH had an effect on lipase activity which showed R2 0.93. The optimum lipase activity produced at pH 6 and on 60 °C, and the lipase stable at pH 6-8 and on 30-70 °C. All metal ions tested were able to increase lipase activity with Ca 2+ ion gave the highest result. Keywords: Lipase, KC4J mutant, Central Composite Design, Oil Palm Waste.